Impotence and the natural explanation of bewitchment: Wolfgang Reichart's medical case report on the loss of "potentia coeundi" - Rubeis, Giovanni; Ursin, Frank; Steger, Florian (Early science and medicine, 2020)
Wolfgang Reichart (1486-c. 1547) was a humanist and a town physician of Ulm. His work consists of a largely unpublished collection of nearly 600 texts. So far, it has been claimed that this compilation only consists of letters and poems. However, we have found a medical treatise, wherein Reichart discusses a case of impotence, its pathophysiology and therapy. One of the crucial aspects in this text is the relationship it describes between witchcraft and medicine. The patient claims that his condition is the result of bewitchment. Reichart accepts witchcraft as a possible aetiological explanation, but claims that since the processes triggered by witchcraft are still natural, the patient can be cured by natural means. Thus, Reichart's approach is an important contribution to the history of medicine and to the history of science of the early modern period. We provide the first edition, translation, and commentary of the text.
DOI falsch 12.11.2020
Gesehen am 12.11.2020